2006
DOI: 10.1007/s10875-006-9036-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms in CCR5, CCR2, CX3CR1, SDF-1 and RANTES in Exposed but Uninfected Partners of HIV-1 Infected Individuals in North India

Abstract: Repeated exposure to human immunodeficiency virus (HIV) does not always result in infection. Understanding the mechanisms that give protection against progressive infection with HIV may help in the development of a vaccine. In order to determine the influence of host genetic factors on HIV resistance, we studied 35 exposed but uninfected (EU) partners of HIV-1 infected individuals for polymorphisms in multiple chemokine and chemokine receptor genes and compared the results with those for 75 HIV-1 seronegative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Our earlier analysis of chemokines and their receptor gene polymorphisms did not show any significant association (35). However, there was elevated spontaneous and HIV gag p24 antigen-induced production of beta chemokines (regulated on activation, normal T-cell-expressed and secreted protein [RANTES], macrophage inflammatory protein 1␣ [MIP-1␣], and MIP-1␤) but not alpha chemokine (stromal cell derived factor 1) by PBMCs in these individuals (36).…”
Section: Discussionmentioning
confidence: 71%
“…Our earlier analysis of chemokines and their receptor gene polymorphisms did not show any significant association (35). However, there was elevated spontaneous and HIV gag p24 antigen-induced production of beta chemokines (regulated on activation, normal T-cell-expressed and secreted protein [RANTES], macrophage inflammatory protein 1␣ [MIP-1␣], and MIP-1␤) but not alpha chemokine (stromal cell derived factor 1) by PBMCs in these individuals (36).…”
Section: Discussionmentioning
confidence: 71%
“…The 380 bp products were subjected to RFLP with the restriction enzyme BseGI, generating two fragments (215 and 165 bp) only when the mutation corresponding to CCR2-64I was present. The wild type allele remained uncut (Suresh et al 2006). For the CCR5 promoter region, primers 5'AAAATCCCCACTAAGATCCTG3' and 5'ATTCATCTAGTCAAAAGCCCAC3' were used .…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…We had earlier reported that Human immunodeficiency virus (HIV) gag antigen-specific T-helper and granule-dependent CD8 T-cell have enhanced activities in exposed but uninfected (ESN) heterosexual partners of HIV type 1-infected individuals in North India [6]. Further we tried to explore the association of gene polymorphisms in CCR5, CCR2, CX3CR1, SDF-1 and RANTES to protection in these individuals [7], but the role of cellular innate immune components remained unexplored. The innate immune system is composed of a wide variety of cellular components including NK cells and dendritic cells which play a significant role in preventing the infection by pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The innate immune system is composed of a wide variety of cellular components including NK cells and dendritic cells which play a significant role in preventing the infection by pathogens. Natural killer (NK) cells, which account for about 10% of peripheral blood lymphocytes, are very effective in producing cytokines like IFNγ, TNFα and GM-CSF which are important regulators of immune responses and haematopoiesis and link the innate to the adaptive immune response through a bidirectional cross-talk with 7 dendritic cells [8,9]. Although low numbers of NK cells have been shown to be associated with rapid progression to AIDS in HIV-infected individuals [10], their role in protection against the establishment of HIV-1 infection remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%